Resistive switching properties and photoabsorption behavior of Ti ion implanted ZnO thin films. Issue 3 (1st February 2022) - Manna, Ashis K.; Dash, P.; Das, Dip; Srivastava, S.K.; Sahoo, P.K.; Kanjilal, A.; Kanjilal, D.; Varma, Shikha
Abstract: We present photoabsorption (PA) response and resistive switching (RS) behavior of ZnO thin films that were ion implanted, at many fluences, with 50 keV Ti ions. Photoluminescence (PL), X-ray photoelectron spectroscopy (XPS), UV–Visible spectroscopy and conductive- Atomic Force Microscopy (c-AFM) have been utilized to study the role of oxygen vacancies (O V ) in the evolution of the PA and RS properties. Grazing incidence X-ray diffraction (GIXRD) and Raman Scattering results suggest an improvement in the crystallinity of the films with ion fluence. Enhancement in oxygen vacancy, with fluence, appears to be responsible for higher photo response in the UV–Vis range. Additionally, engineering of bandgap, exhibiting systematic reduction in bandgap- energy with fluence, introduces enhanced absorption in visible regime. For the films implanted at the highest fluence, an asymmetric RS behavior is observed. A Switching behavior, from a high resistance state to a low resistance state, is demonstrated under positive bias conditions. However, for negative bias conditions a rectifying nature is seen. Oxygen vacancies play a crucial role in the modulation of PA response as well as in RS mechanism. Migration of these oxygen vacancies contribute to the formation of conducting filament which may be crucial for the observation of RS phenomenon at the highest fluence.